2003
DOI: 10.4049/jimmunol.171.7.3372
|View full text |Cite
|
Sign up to set email alerts
|

Airway Eosinophils Accumulate in the Mediastinal Lymph Nodes but Lack Antigen-Presenting Potential for Naive T Cells

Abstract: Asthma is characterized by infiltration of the airway wall with eosinophils. Although eosinophils are considered to be effector cells, recent studies have reported their ability to activate primed Th2 cells. In this study, we investigated whether eosinophils are capable of presenting Ag to unprimed T cells in draining lymph nodes (DLN) of the lung and compared this capacity with professional dendritic cells (DC). During development of eosinophilic airway inflammation in OVA-sensitized and challenged mice, CCR3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 20 publications
0
75
2
Order By: Relevance
“…(21) We show here that human eosinophils are also effective APC for a variety of antigens in vitro, able to evoke Th proliferative responses comparable in magnitude to those seen when paired PMBC samples are challenged with the same antigen. Thus, human eosinophil presentation to Th cells is limited neither to peptide antigens nor superantigens that do not require processing, as has been suggested, (11,16) but may instead contribute to responses against many different proteins. Whether such activity as APC in vitro is replicated in vivo remains to be established, but would be consistent with the increasingly accepted view that human eosinophils have immune regulatory, as well as effector, roles.…”
Section: Eosinophil Expression Of Mhc Class II and Co-stimulatory Molmentioning
confidence: 84%
See 2 more Smart Citations
“…(21) We show here that human eosinophils are also effective APC for a variety of antigens in vitro, able to evoke Th proliferative responses comparable in magnitude to those seen when paired PMBC samples are challenged with the same antigen. Thus, human eosinophil presentation to Th cells is limited neither to peptide antigens nor superantigens that do not require processing, as has been suggested, (11,16) but may instead contribute to responses against many different proteins. Whether such activity as APC in vitro is replicated in vivo remains to be established, but would be consistent with the increasingly accepted view that human eosinophils have immune regulatory, as well as effector, roles.…”
Section: Eosinophil Expression Of Mhc Class II and Co-stimulatory Molmentioning
confidence: 84%
“…(15) Consistent with APC function, murine eosinophils home to lymphoid tissue and provide a second signal for T cell activation through the expression of key co-stimulatory molecules such as CD80 and CD86. (16,17) Although it has been demonstrated that human eosinophils can express CD86 when taken from hypereosinophilic patients, (18) or stimulated with IL-3, (19) it is unclear how commonly, or in what circumstances, they display such co-stimulatory molecules. There are also reports that human eosinophils can process and present antigen to activate specific T cells, (20) but, again, it remains to be established how widespread is such ability in different individuals and for different antigens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in mice have shown that eosinophils are capable of transmigrating to lymphoid tissues and presenting antigens to lymphocytes (71,72). Although antigen presentation to naı¨ve T cells by eosinophils is still controversial, there is a consensus that eosinophils can present antigen to previously activated T cells, supporting the notion that eosinophils can further influence established immune responses (73).…”
Section: Eosinophil Modulation Of Tissue Inflammationmentioning
confidence: 87%
“…Because the chemokine receptor CCR3 has been proposed to orchestrate eosinophil migration into the lung, we investigated the percentage of CCR3-expressing leukocytes in lung tissue after enzymatic digestion (31). In prenatally stressed mice, an increased percentage of chemokine receptor CCR3 ϩ cells among lungderived leukocytes could be detected (Fig.…”
Section: Prenatal Stress Increases Ccr3 ϩ Cells In Ova-sensitized Adumentioning
confidence: 99%